Pengaruh Arus Kas Bebas, Investment Opportunity Set, dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Kepemilikan Institusional sebagai Variabel Moderasi - Vanenza, Desrimayana Putri; Hizazi, Ahmad; Olimsar, Fredy (Jurnal Akuntansi & Keuangan Unja, 2026)
This study aims to determine the effect of Free Cash Flow, the Investment Opportunity Set, and Firm Size on Firm Value, with Institutional Ownership serving as a moderating variable. This is a quantitative study. The population consists of Consumer Non-Cyclical companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample was selected using purposive sampling, resulting in a total of 101 companies. The study utilizes secondary data obtained from the official Indonesia Stock Exchange website. Data analysis was conducted using panel data regression with E-Views 13 software. The results indicate that Free Cash Flow has a negative effect on Firm Value and the Investment Opportunity Set has a positive effect on Firm Value, whereas Firm Size has no effect on Firm Value. Institutional Ownership positively moderates the effect of Free Cash Flow on Firm Value. However, Institutional Ownership negatively moderates the effects of the Investment Opportunity Set and Firm Size on Firm Value.